Hypothalamic Proopiomelanocortin Is Necessary for Normal Glucose Homeostasis in Female Mice - Alsina, Ramiro; Trotta, Milagros; Bumaschny, Viviana Florencia (Frontiers in Endocrinology, 2018)
The arcuate nucleus of the hypothalamus is a key regulator of energy balance and glucose homeostasis. In particular, arcuate proopiomelanocortin (POMC) neurons inhibit food intake, stimulate energy expenditure and increase glucose tolerance. The interruption of insulin or glucose signaling in POMC neurons leads to glucose intolerance without changing energy homeostasis. Although it was previously shown that POMC neurons are necessary for normal glucose homeostasis, the participation of POMC neuropeptide, by mechanisms independent of energy balance, remains to be demonstrated. To study the role of POMC in the regulation of glucose homeostasis, we performed glucose and insulin tolerance tests in non-obese mice lacking hypothalamic POMC expression. We found that POMC deficiency leads to glucose intolerance and insulin resistance in female mice before the onset of obesity or hyperphagia. Conversely, POMC deficiency does not impair glucose homeostasis in non-obese male mice. Interestingly, females completely normalize both glucose and insulin tolerance after genetic POMC restoration. Next, to further study sex dimorphism of POMC neurons regarding glucose homeostasis, we measured glucose-elicited changes in C-FOS by performing immunofluorescence in brain slices of POMC-EGFP mice. Remarkably, we found that glucose-induced C-FOS expression in POMC neurons is more than 3-fold higher in female than in male mice. Altogether, our results reveal a key role of arcuate POMC in the regulation of glucose homeostasis in females. Since POMC reactivation completely reverses the diabetogenic phenotype, arcuate POMC could be a potential target for diabetes therapy.